Can UKA after KineSpring system failure be a viable option? A case report - Niccoli, Giuseppe; Di Benedetto, Paolo; Salviato, Daniele; Beltrame, Alessandro; Gisonni, renato; Cainero, Vanni; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the Work: The KineSpring System is an alternative treatment offered in selected symptomatic patients suffering from mild to moderate medial knee osteoarthritis (OA). This device reduces medial compartment loads in the OA knee without compromising the integrity of the lateral or patellofemoral knee compartments, maintaining the normal knee anatomy. Currently, papers about KineSpring System installation show promising results. The current authors describe a case of unicompartmental knee arthroplasty (UKA) employed to treat medial knee OA after Kinespring system failure. Methods: A 64-year old male patient presented to our hospital after failure of a Kinespring system implantation into his left knee at an external hospital, where the outcomes obtained were not satisfactory. The surgical options discussed with the patient were the TKA or medial UKA. A medial UKA was preferred by the patient. Results: One year from UKA, the patient complained of frequent joint effusions and weight bearing pain despite a good ROM without radiographic signs of implant loosening. Therefore, after two years we replaced UKA with total knee arthroplasty (TKA). Conclusions: Further experience is needed to provide reliable clinical data about the results of the UKA after KineSpring System discharge.